Exploratory proteome profiling in patients with peripartum cardiomyopathy – a biomarker study on the EORP cohort. (3rd October 2022) - Kodogo, V; Viljoen, C; Chakafana, G; Hoevelmann, J; Jackson, A; Al-Farhan, H; Goland, S; Tromp, J; Van Der Meer, P; Karaye, K; Kryczka, K; Mebazaa, A; et al.
Abstract: Background: The diagnosis of peripartum cardiomyopathy (PPCM) remains challenging as heart failure symptoms may also occur during normal pregnancy. This is further aggravated by the absence of biomarkers specific for diagnosis or prognosis of women with PPCM. Indeed, current evidence from the EURObservational Research Programme (EORP) Registry, an ongoing prospective, international, multicentre, observational registry for women with PPCM, report that the time to diagnosis after symptom onset varies from 19.4 to 38.3 days. Aims: We performed exploratory serum proteome profiling on patients with PPCM, as compared with healthy postpartum mothers, to uncover novel protein biomarkers that would further our understanding of the pathogenesis of the disease and enhance diagnostic evaluation. Methods: Demographic and clinical data, as well as serum samples were collected from 84 patients with PPCM from seven EORP participating countries and 29 healthy controls (HC) from South Africa. Serum proteomic profiling was conducted using DIA-based label-free quantitative (LFQ) LC-MS at the time of diagnosis from depleted serum samples. Mass spectrometry data were analyzed by Spectronaut v15 using a study-specific spectral library. Proteomic statistical analysis was performed using Perseus version 2.0.3.0 (FDR=0.05; S=0.1). Results: Patients with PPCM had advanced heart failure (50% had New York Heart Association functional classes III/IV, mean left ventricular ejection fraction [LVEF] of 33.5%±9.3 [vs 57.0±8.8 in HC, p<0.001]). Amongst the 329 proteins that were identified in the serum samples, 17 proteins were significantly differentially upregulated and 18 downregulated in patients with PPCM as compared to the HC (all p<0.05; Figure 1). Adiponectin (log fold change 1.378, p=0.001), pregnancy-specific beta-1-glycoprotein 1 (1.207, p=0.022), disintegrin metalloproteinase domain-containing protein 12 (1.185, p=0.039), peptidyl-prolyl cis-trans isomerase (1.182, p=0.031) and sulfhydryl oxidase 1 (1.101, p=0.004) were among the upregulated proteins, whilst immunoglobulin kappa variable 2–29 (0.856, p=0.029), ficolin-3 (0.898, p=0.001), platelet basic protein (0.917, p=0.006) and thrombospondin-1 (0.930, p=0.043) were among the downregulated. Gene ontology indicated that thrombospondin receptor activity, fibronectin-binding, and vascular endothelial growth factor receptor 2 binding among the most significant regulated molecular functions. The area under the curve (AUC) of the top 10 up-regulated biomarkers ranged from 0.61–0.68 (p<0.05). Conclusion: Salient biological themes related to immune response proteins, inflammation, fibrosis, angiogenesis, apoptosis, and blood coagulation were identified to be predominant in PPCM versus HC. This indicates the complex pathophysiological mechanisms of PPCM. The newly identified proteins warrant further studies to evaluate their potential use as diagnostic and prognostic markers for PPCM. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): 1. EurObservational Research Programme in conjunction with the Heart Failure Association of the European Society of Cardiology Study Group on Peripartum Cardiomyopathy2. Cape Heart Institute, University of Cape Town, South Africa